Intravenous lipid emulsions in the critically ill: an update. Issue 4 (August 2016) - Manzanares, William; Langlois, Pascal L.; Hardy, Gil
Abstract : Purpose of review: Purpose of the review is to summarize recent research addressing the role of intravenous lipid emulsions (IVLEs) in the critically ill. Recent findings: Soybean oil-based IVLEs, which are high in the omega-6 polyunsaturated fatty acids, have been largely used in parenteral nutrition over the last several decades. However, it is now generally accepted that the higher content of phytosterols and polyunsaturated fatty acids in soybean oil IVLE may adversely affect the immunological and inflammatory status of the critically ill. In the last few years, alternative IVLEs with lower soybean oil content have been associated with important improvements in clinical outcomes, such as mortality, mechanical ventilation days, and ICU length of stay. Olive oil and fish oil IVLEs have been reported to reduce the incidence of infections, with no clear benefits in other clinical outcomes. Despite the promising results with these new parenteral nutrition strategies, the optimum composition, dosage and indication for alternative IVLEs still remain controversial. Nevertheless, according to current knowledge alternative IVLEs may be associated with improved clinical outcomes and should be considered in critically ill patients requiring parenteral nutrition. Summary: There is a growing body of evidence suggesting that improved clinical outcomes can be achieved with selective use of alternative IVLEs in parenteral nutrition regimens for the critically ill. More high quality trials are needed, to better evaluate the efficacy of alternative IVLEs.